2018
DOI: 10.6024/jmbai.2018.60.2.2060-15
|View full text |Cite
|
Sign up to set email alerts
|

New record of Abralia (Heterabralia) siedleckyi Lipinski, 1983 (Cephalopoda: Enoploteuthidae) from south-eastern Arabian Sea with some remarks about its biology

Abstract: Specimens of oceanic squid, Abralia (Heterabralia) siedleckyi Lipinski, 1983 were collected from the southeastern Arabian Sea using midwater trawl (horizontally at 200 m depth) during night operations in two cruises on 18 April 2015 and 26 February 2017. Description and morphological measurements of the specimens are provided. The record of this mesopelagic squid from the Arabian Sea is an addition to the cephalopod fauna of the Indian Ocean and India. The statolith based age analysis indicates that a 29.1 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…The absolute fecundity of Abralia andamanica from the Arabian Sea was estimated to range from 2400 to 3200 oocytes (Amelekhina 1983). The mean oocyte number was 251 in the oviducts of Abralia verany Rüppell, 1844 from the eastern Mediterranean Sea (Salman and Laptikhovsky 2005), and 284 in A. siedleckyi from the Arabian Sea (Sajikumar et al 2019b), figures which are comparable to our estimated mean of 274 oocytes. indicated that A. trigonura is a multiple spawner, and Laptikhovsky (1999) showed that spawning is prolonged and intermittent for enoploteuthids.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The absolute fecundity of Abralia andamanica from the Arabian Sea was estimated to range from 2400 to 3200 oocytes (Amelekhina 1983). The mean oocyte number was 251 in the oviducts of Abralia verany Rüppell, 1844 from the eastern Mediterranean Sea (Salman and Laptikhovsky 2005), and 284 in A. siedleckyi from the Arabian Sea (Sajikumar et al 2019b), figures which are comparable to our estimated mean of 274 oocytes. indicated that A. trigonura is a multiple spawner, and Laptikhovsky (1999) showed that spawning is prolonged and intermittent for enoploteuthids.…”
Section: Discussionsupporting
confidence: 84%
“…The oldest mature female was 177 days old, suggesting that A. andamanica may have a lifespan of about 6 months in the tropical Arabian Sea, which is similar to that reported for A. trigonura from the Hawaiian waters . A mature female individual of Abralia siedleckyi Lipinski, 1983 (29 mm DML) from the Arabian Sea had an age of 93 days with a daily growth rate of 0.31 mm DML/day (Sajikumar et al 2019b). It has been found that enoploteuthids including Abraliopsis atlantica, Abraliopsis morisii and Enoploteuthis leptura grow slowly and have short lifespans (Arkhipkin and Murzov 1990, Arkhipkin 1994, 1996a.…”
Section: Discussionmentioning
confidence: 99%
“…Other important morphological features that our specimens had were the three hooks on the tentacular club and photophore pattern on the ventral region of the eyeball, and five complex photophores, consistent with the description by Sajikumar et al . (2018): two terminal oval, creamy white, opaque organs (posterior is extra-large) and three intermediate orange organs. The dorsal part of the eyelid bore 16 black photophores.…”
Section: Resultsmentioning
confidence: 99%
“…Our knowledge of the known geographic distribution ranges of A. ( H. ) siedleckyi (Lipinski, 1983; Sajikumar et al ., 2018) have been expanded to western to 16°N, placing this species off Western Sahara, inside CCLME waters.…”
Section: Discussionmentioning
confidence: 99%